Evaluation of 2-(salicylideneimino) thiophenol and other Schiff bases as bronze corrosion inhibitors by electrochemical techniques and surface analysis. (March 2019) - Monticelli, C.; Balbo, A.; Esvan, J.; Chiavari, C.; Martini, C.; Zanotto, F.; Marvelli, L.; Robbiola, L.
Highlights: New Schiff bases tested as bronze corrosion inhibitors in concentrated acid rain. 2-(Salicylideneimino) thiophenol (SITP) afforded η = 100% after 480 h immersion. Duplex protective film formed: adsorbed SITP molecules over a Cu(I)-SITP layer. Phosphates (P) added to SITP produced higher resistance against localized attack. SITP and SITP + P hindered bronze decuprification in concentrated acid rain. Abstract: In this research, different Schiff bases were synthesized and tested as bronze corrosion inhibitors in concentrated synthetic acid rain at pH 3.3. Some of them showed good inhibiting effects, as detected by EIS and polarization curve recording. The most efficient inhibitor (2-(salicylideneimino) thiophenol, SITP) was also tested with addition of sodium dihydrogen phosphate (P). P improved the surface film resistance against breakdown phenomena. XPS and SEM investigations showed that SITP and SITP + P significantly hinder decuprification. Moreover, SITP forms a protective layer on bronze, composed of both Cu(I)-SITP complexes and adsorbed inhibitor molecules. Cu(II) phosphates were also detected with P addition.